Rational Beliefs and Security Design - Garmaise, Mark (Review of Financial Studies, 2001)
This article studies the security-design problem of a cash-constrained firm facing investors with diverse beliefs. Investor “rational beliefs” are modeled as varying and yet rational in the sense of Kurz (1994a). With two investors, optimal designs are similar under rational beliefs and rational expectations. With many investors, however, optimal securities under rational beliefs maximize investor differences of opinion, while under rational expectations optimal designs minimize disagreements. We demonstrate that the common practice of issuing multiple securities backed by a single asset is optimal under rational beliefs but not under rational expectations. Researching market beliefs can create substantial value for firms.